Implementation of the Tahfiz Al-Quran Education Program in Malaysian Polytechnics to Strengthen Islamic Studies - YUSAK, Yusni Mohamad; IKHWAN, Afiful; RAZAK, Khadijah Abdul; ANWAR, Saiful (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Numerous reforms are making Islamic studies more accessible to Malaysian students in various polytechnics. The most significant reforms are the program structure, content, course credit depreciation, and meeting hours. The proposed reforms are projected to enhance Islamic Studies at the polytechnics to help produce graduates who can apply al-Quran al-Karim daily. The Malaysian Polytechnic’s Tahfiz al-Quran al-Karim Education Program (Tahfiz-TVET) is one of the new reforms projected to help strengthen students’ knowledge of Islamic Studies. This study explores Malaysian Polytechnic’s Tahfiz al-Quran al-Karim Education Program (Tahfiz-TVET) and its link with Islamic Studies at the Sultan Salahuddin Abdul Aziz Shah Polytechnic. This study will explore the JAKIM-Polytechnic Tahfiz al-Quran Certification Program. In addition, it will also expose the Islamic Studies courses in Mata Pelajaran Pengajian Umum (MPU) (General Studies Unit) at the Sultan Salahuddin Abdul Aziz Shah Polytechnic. This study contends that the JAKIM-Poli Tahfiz Certification programme at the Sultan Salahuddin Abdul Aziz Shah Polytechnic has religious and social importance. The religious significance is that the program will assist in producing graduates with a solid Islamic foundation and (akhlaq) good virtue, morality, and etiquette. Both programmes will also help produce technicians and engineers to meet the nation’s professional and social job demands. Thus, the program’s ultimate goal is to develop holistic Muslim professionals.